The unbroken thread: discovering the wisdom of tradition in an age of chaos - Ahmari, Sohrab (Convergent, 2021)
How do you justify your life? -- Is God reasonable? -- Why would God want you to take a day off? -- Can you be spiritual without being religious? -- Does God respect you? -- Does God need politics? -- How must you serve your parents? -- Should you think for yourself? -- What is freedom for? -- Is sex a private matter? -- What do you owe your body? -- What's good about death? -- Conclusion: A letter to Maximilian.